Stepper motor controller / Mohd Hafiz Azmi and Mohd Quyyum Ab Rahman - Azmi, Mohd Hafiz; Ab Rahman, Mohd Quyyum (2005)
Stepper Motors are elctromechanical motion devices, which are used primarily to convert information in digital form to mechanical motion. These motors rotate at a predetermined angular displacement in response to a logic input. Whenever stepping from one position to another is required, the stepper motors are generally used. As their name implies, stepper motors rotate in discrete steps, each step corresponding to a pulse that is supplied to one of its stator windings. Step sizes may range from less than a degree to 15° or larger. The stepper motor can turn clockwise or counter-clockwise, depending upon the sequence of the pulses that are applied to the windings. Typical applications include paper feed motors in typewriters and printers, positioning of print heads, pens in XY plotters, recording heads in computer disk drives, worktable and tool positioning in numerically controlled machining equipment and any other application where rotation in both directions, angular incremental changes, and continuous or stepwise displacements are required.